Estrategias de logística y su incidencia en el proceso de distribución en la empresa Doña Empanada en la ciudad de Babahoyo, periodo 2023. - Burgos Espinoza, Rubén Darío (2024)
In a highly competitive and dinamia business envaronen, companies must adapt quickly to ensure their survival and growth. Logistics plays a crucial role in the supply chain, directly impacting customer satisfaction, operational efficiency and business sustainability. Doña Empanada, a company that distributes empanadas in Babahoyo, needs to optimize its logistics estratego to increase its competitiveness. This study aims to compare the effectiveness of Doña Empanada's logistics strategies in promoting its products and identify areas of ímprobamente to optimize its operations, increase competitiveness and promote sustainability. To achieve this objective, three specific goals have been defined. The first is to investigate customer satisfaction with Doña Empanada's delivery services, considering that this satisfaction is a key indicator of business success. The second goal is to examine the efficiency of transportation and storage measures, essential to maintaining the freshness and quality of perishable products. The third goal is to analyze the productivity of information technology systems implemented in 2023, which are essential to improve warehouse and supply chain efficiency by providing real-time data. Research line: Administration, Economics and Finance Research sub-line: Business Management and Administration, International Trade, Economics and Finance, Technology and Electronic Commerce, Sustainable Development and Social Responsibility.